A Systematic View of the MLO Family in Rice Suggests Their Novel Roles in Morphological Development, Diurnal Responses, the Light-Signaling Pathway, and Various Stress Responses - Nguyen, Van N. T.; Vo, Kieu T. X.; Park, Hyon; Jeon, Jong-Seong; Jung, Ki-Hong (Frontiers in Plant Science, 2016)
The Mildew resistance Locus O (MLO) family is unique to plants, containing genes that were initially identified as a susceptibility factor to powdery mildew pathogens. However, little is known about the roles and functional diversity of this family in rice, a model crop plant. The rice genome has 12 potential MLO family members. To achieve systematic functional assignments, we performed a phylogenomic analysis by integrating meta-expression data obtained from public sources of microarray data and real-time expression data into a phylogenic tree. Subsequently, we identified 12 MLO genes with various tissue-preferred patterns, including leaf, root, pollen, and ubiquitous expression. This suggested their functional diversity for morphological agronomic traits. We also used these integrated transcriptome data within a phylogenetic context to estimate the functional redundancy or specificity among OsMLO family members. Here, OsMLO12 showed preferential expression in mature pollen; OsMLO4, in the root tips; OsMLO10, throughout the roots except at the tips; and OsMLO8, expression preferential to the leaves and trinucleate pollen. Of particular interest to us was the diurnal expression of OsMLO1, OsMLO3, and OsMLO8, which indicated that they are potentially significant in responses to environmental changes. In osdxr mutants that show defects in the light response, OsMLO1, OsMLO3, OsMLO8, and four calmodulin genes were down-regulated. This finding provides insight into the novel functions of MLO proteins associated with the light-responsive methylerythritol 4-phosphate pathway. In addition, abiotic stress meta-expression data and real-time expression analysis implied that four and five MLO genes in rice are associated with responses to heat and cold stress, respectively. Upregulation of OsMLO3 by Magnaporthe oryzae infection further suggested that this gene participates in the response to pathogens. Our analysis has produced fundamental information that will enhance future studies of the diverse developmental or physiological phenomena mediated by the MLO family in this model plant system.